Improving Students Reading Comprehension Of Procedural Text Using KWL Strategy - Hanura Hanura; Ali Akbar Jono (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
This study employed a classroom action research design to determine how the KWL strategy could be applied successfully in enhancing students' reading comprehension especially in procedural text. There are four stages in this research. Consist of pre-assessment and cyles 1 until 3. Planning, Acting, Observing, and reflecting were all part of each cycle. Student’s reading achievements were analyzed in each cycle to see their reading comprehension, including pre-assessment. Observations, questionnaires, and interviews were used to collect qualitative data, while test were used to collect quantitative data. This study gets some results. The first is that the KWL strategy could improve students reading comprehension of procedural text and increase students score in reading. The strategy could also develop students' reading comprehension skills in terms of activating prior knowledge, explicit knowledge, implicit information, and word references, as well as recognizing word meanings dependent on context. The strategy was also improved the classroom atmosphere.